Regulatory Aspects of Servitisation: Study Materials for Global Law Course - Hojnik, Janja (University of Maribor Press, 2024)
This course material was prepared as a support for a lectures series under Global Law Programme organised by the Catholic University Leuven (Belgium), Faculty of Law and Criminology. The course dealt with EU regulatory challenges arising from the servitisation of manufacturing and the related sustainability and digitalisation process in the EU economy. Servitisation is a complex interdisciplinary concept that essentially stands for bringing together products and services. Servitization as an economic megatrend reflects consumers’ oriented business models, offering not just products to the buyers, but solutions to their problems. This solution offering is enhanced by digitalisation of the economy that makes the relationship between product-service providers and their customers easier to maintain due to various mechanisms of distant communication and monitoring. Moreover, servitisation is at the centre of the endeavours to establish a more sustainable circular economy. Adding services to products can prolong their consumption time, decrease the amount of materials needed for certain effect and improve waste management. Increasingly, however, it is clear that servitisation is not just related to environmental sustainability, but social as well. These services often require people to be performed and digital applications tend to decrease their rights as workers to the benefit of the owners of these applications.